A hands-on classroom activity to teach science concepts for students with visual impairment. (2nd October 2019) - Kızılaslan, Aydın; Zorluoglu, S. Levent; Sözbilir, Mustafa
Abstract: Students with visual impairments have the same span of cognitive abilities as their peers, but science instruction typically relies very heavily on vision. The preponderance of visually oriented and visually complex science concepts poses significant challenges to learning among students with visual impairment. This study is engaging, hands-on ideas that can be done to teach thermal insulation concept for students with visual impairment in the classroom. 8 students including 2 blind students participated in the study.